The Method for Calculating the Contact Ｒesistance Used Fuzzy System Optimized by Ｒecursive Least Square - WANG Gang; WANG Zhi-jun; ZHAO Li-li; LIU Ya-pei; WANG Xu; HAO Xiang-yu (Journal of Harbin University of Science and Technology)
The contact resistance is modeled by fuzzy system for the characteristics. The experiment is designed and training data and testing data is got. Using training data，fuzzy system is trained，the model of contact resistance is set up，and training algorithm is recursive least square combined tabu search. The model of contact resistance is built through regression analysis. The two models are tested by testing data，the result is compared， and the model based on fuzzy system is better. The result shows that fuzzy system is suitable for calculating contact resistance.